Prevalence of hypothyroid dysfunction among third trimester pregnant women and its effect on maternal and fetal outcome - Kanawala, Arundati; Shekhawat, Gulab Singh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Thyroid disorders are the predominant endocrinological afflictions of pregnancy that if were to affect the mother and her child, would lead to various complications. Methods: A randomized study among 450 third trimester admitted cases for any indication were subjected to thyroid functions by TSH, Free T4 and TPO Ab. Total 61 mothers (54 hypothyroidism and 7 sub clinical hyperthyroidism) had thyroid dysfunction. These 54 hypothyroid mothers were further evaluated during the remaining course of gestation for feto-maternal outcomes. Results: Out of 450 third trimester ANC cases 61(13.5%) had deranged thyroid functions in third trimester. Out of 61patients, 18 (29.50%) patients had TPO Ab positive. Prevalence of subclinical hypothyroidism, overt hypothyroidism, and subclinical hyperthyroidism was 9.6%, 2.45%, and 1.5%, respectively. Anemia was found in 9.3% of SCH and 27.3% cases in OH cases. Preeclampsia was found in 16.2% cases of SCH and 18.2% cases in OH cases. Gestational diabetes mellitus was noticed among 16.27% cases of SCH and 18.18% cases of OH. Previous abortions were present among 65.1% cases of SCH and 45.45% cases of OH. Placental abruption and cardiac failure were observed in 4.65% and 2.34% of SCH only. Cesarean delivery occurred in 18.6% of SCH and 36.36% of overt hypothyroidism. Conclusions: This study concludes a high prevalence of thyroid disorders as subclinical hypothyroidism (9.6%), overt hypothyroidism (2.5%) and subclinical hyperthyroidism (1.5%) in third trimester pregnancy.